Pengaruh suku bunga, inflasi, nilai tukar, dan PDB terhadap kredit investasi pada perbankan di Indonesia - Fauzianto, Yuliana; Nurjanah, Rahma; Mustika, Candra (Jurnal Paradigma Ekonomika, 2025)
The purpose of this research is to determine the development of interest rates, inflation, exchange rates and GDP on investment credit in banking in Indonesia to analyze the influence of interest rates, inflation, exchange rates and GDP on investment credit in banking in Indonesia. This research uses time series data for the period 2000 to 2023 with a quantitative descriptive analysis method and uses multiple linear regression analysis tools with the Ordinary Least Square method. The data analysis technique is multiple linear regression. Based on the results, it can be concluded that interest rates, exchange rates and GDP have a significant effect on investment credit, while inflation has no significant effect on investment credit in banking in Indonesia.